ANALYSIS OF THE MAIN RISK FACTORS IN PATIENTS WITH CHRONIC HEART FAILURE OF ISCHEMIC ETIOLOGY AND THEIR ADHERENCE TO TREATMENT (World Bulletin of Public Health, 2024)
Chronic heart failure of ischemic etiology is not only a medical but also a social problem due to its significant prevalence, high mortality rate and high costs of treatment of patients. Despite certain advances in the study of pathogenesis, clinic and treatment, this pathology still remains the most common, severe and prognostically unfavorable complication of all diseases of the cardiovascular system. The presence of several risk factors, low adherence to drug and nondrug treatment leads to the progression of CHF, deterioration of quality of life and increased frequency of hospitalizations.